Statistical modelling of permanent cropland availability and population growth with effect to crop production in Nigeria - Ode, Oga; Mutah, Wadai (Lithuanian Journal of Statistics, 2025)
This study investigates the long-run and short-run interplay between crop production, population growth and permanent cropland in Nigeria over a 61 year period spanning 1961–2021 using World Development Indicators (WDI) data and a vector autoregressive (VAR)/vector error correction model (VECM) framework. Unit root tests (ADF and Phillips-Perron) confirm that the series are integrated of order one or I(1), and the Johansen test for cointegration establishes the presence of at least one long-run equilibrium relationship. The VECM results reveal that cropland expansion significantly and positively impacts crop production, whereas population growth exerts a negative influence, emphasizing the dual role of demographic pressure as both a driver of demand and a constraint on supply. The VECM result further shows a high rate of adjustment from disequilibrium to long-run equilibrium. Diagnostic checks confirm model adequacy, while impulse-response analysis shows that shocks to crop production stimulate sustained cropland expansion, whereas shocks to population growth exert a negative pull. Overall, the findings underscore the importance of policies that balance land expansion and agricultural productivity with demographic management strategies, to secure long-term food security in Nigeria.